2019
DOI: 10.4018/ijphim.2019010106
|View full text |Cite
|
Sign up to set email alerts
|

BPMN Coordination and Devs Network Architecture for Healthcare Organizations

Abstract: The adoption of business processes (BP) can help healthcare providers in structuring the way information systems and people have to interact. Business process management (BPM) is a methodology that structures a way of representing system processes. At the same time, the human resources are organized in identified or implicit structures that allows individuals to exchange information either related to their work function or not. Nevertheless, the human organizations structure and communication channels are not,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…While these examples are more in line with digital health services at the individual level than at the population level, it is important to acknowledge that – in order for new or repurposed DPH tools to be taken up at larger scale – the receiving system needs to be ready to assimilate the innovation, both in terms of technological compatibility and restructuring of work processes and pathways. 34 , 35 , 36 , 37 System readiness, in this line of reasoning, is fostered by exposure to and awareness of successful innovations in either the same domain elsewhere or a different domain within the same overarching system (i.e. healthcare or public health) and can occur at a national, organisational, community, and individual level.…”
Section: System Readiness For Digital Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…While these examples are more in line with digital health services at the individual level than at the population level, it is important to acknowledge that – in order for new or repurposed DPH tools to be taken up at larger scale – the receiving system needs to be ready to assimilate the innovation, both in terms of technological compatibility and restructuring of work processes and pathways. 34 , 35 , 36 , 37 System readiness, in this line of reasoning, is fostered by exposure to and awareness of successful innovations in either the same domain elsewhere or a different domain within the same overarching system (i.e. healthcare or public health) and can occur at a national, organisational, community, and individual level.…”
Section: System Readiness For Digital Public Healthmentioning
confidence: 99%
“…That said, in order for the population to become actively involved in DPH and for DPH to improve the social health experience, 39 a more horizontal design of DPH needs to be normalised and healthcare pathways need to be reconsidered in light of existing and emerging technologies. 37 , 39 For instance, a DPH initiative using the technology currently in use to detect information relating to COVID-19 in social media posts could make use of the habit of the general population to search for health-related information through (social) media networks in order to provide them with contact details for relevant health professionals. 40 To develop these technologies, public and private actors should not only ensure their technological infrastructure is compatible, but also align their values, vision, and resources.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…In this paper [26], the authors conducted a systematic review of the literature, where they identified that few authors have explored elements of user interaction in their works. The purpose of the paper [27] was to study the feasibility of combining the business processes (BP) with agent-based models to improve performance, manage resources, and ensure coordination between them. The authors present multi-agent solutions representing social networks in the healthcare domain associated with a Business Process Management (BPM) of patient pathways.…”
Section: Related Workmentioning
confidence: 99%
“…According to the field of our research, we have reviewed the articles, respectively, for BPM in health care in references (Pufahl et al ., 2022; Kirikkayis et al ., 2022; Basri et al. , 2021; Sbayou et al ., 2019), BPM in clinical processes including (Bianchi et al. , 2021; Pereira et al ., 2020; Combi et al ., 2021; Becker et al ., 2020; Pasichnyk et al.…”
Section: Introductionmentioning
confidence: 99%